A review of the utilization of coal bottom ash (Cba) in the construction industry - Mohammed S.A.; Koting S.; Katman H.Y.B.; Babalghaith A.M.; Patah M.F.A.; Ibrahim M.R.; Karim M.R. (MDPI AG, 2023)
bottom ash; construction industry; physicochemical property; recycling